ENGLISH EDUCATION MASTER STUDENTS’ PERCEPTIONS ON THEIR SELF-EFFICACY IN EFL SPEAKING LEARNING CONTEXTS - Kristian Florensio Wijaya (Sanata Dharma University, Yogyakarta, 2021)
AbstractSelf-efficacy should be fully integrated as one of the mainstays assisting multiverse EFL academicians to achieve greater speaking learning achievements, improve their actual communicative competencies, and justify their misconceptions of L2 speaking learning enterprises. Corresponding with these 3 aforementioned advantages, the full activation of robust self-efficacy will potentially allow EFL academicians to show greater effortful actions, resilience, motivation, and commitment to relentlessly forge their L2 communicative competencies in the presence of adverse speaking learning situations. This qualitative study was conducted in the support of the narrative inquiry approach to yield rejuvenated facts, trustworthy truth, and apparent evidence for worldwide EFL educationalists concerning the significance of self-efficacy implementations in diverse wide-ranging L2 speaking classroom vicinities. Two major positive influential factors are deemed as both internal and external factors affecting the luxuriant proliferation of striking L2 speaking skills as well as self-efficacy levels advancement namely the induction of long-life speaking learning endeavor and supportive speaking learning environments. For the future betterment of self-efficacy and EFL speaking studies, varied relevant research instruments need to be mutually accompanied by a considerable number of research participants to produce more significant research results contributing a richer understanding of affective second language learning fields. Keywords: Self-efficacy, EFL speaking, narrative inquiry